Internal structure change of carbon tool steel after heat treatment - Chew, Chun Chi (2008)
Carbon steel is normally used in the manufacture of chisels, tools parts where high hardness is required to maintain a sharp cutting edge. But, the most common problems we encountered are the short life of the tool. Hence, it is important to use a suitable medium for quenching process to extend the tool life. The main objective of this project is to analyze the internal structure of carbon steel after quenching process. Eventually, the most suitable medium for quenching carbon steel AISI 1045 will be recommended. A carbon steel rod with a diameter of 1.6cm was cut into the size of 2cm in length. Six specimens in the same dimensions were prepared. Each specimen’s surface was ground by using different grade of abrasive paper. After the grinding process, three out of six specimens were undergoing quenching process for one day in three different types of medium; which is oil, water and coolant. However, another three specimens were quenched for one day. After quenching process, all specimens were grinding again to retain shining surface. Diamond liquid was used to polish the surface and then the surface was etched by 2% nital. The internal structure of water and coolant quenching formed finer pearlite while oil quenching formed coarser pearlite. The structures formed have high hardness value ranged from 20.3 HRC to 47.5 HRC. The results were analyzed by using Rockwell hardness tester. The internal structure of specimen was analysed using microscope image analyser equipment and the results were displayed onto computer screen.